2012
DOI: 10.1016/j.biocel.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, heterologous expression and functional characterization of a novel translationally-controlled tumor protein (TCTP) family member from Loxosceles intermedia (brown spider) venom

Abstract: Envenoming with brown spiders (Loxosceles genus) is common throughout the world. Cutaneous symptoms following spider bite accidents include dermonecrosis, erythema, itching and pain. In some cases, accidents can cause hypersensibility or even allergic reactions. These responses could be associated with histaminergic events, such as an increase in vascular permeability and vasodilatation. A protein that may be related to the effects of spider venom was identified from a previously obtained cDNA library of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 56 publications
5
52
0
Order By: Relevance
“…A transcript resembling the TCTP was consistently expressed at high levels across all tissue types in our focal species (table 3) and also expressed at high levels previously in acrorhagi of A. elegantissima (see Macrander, Brugler, et al 2015). Venomous TCTP toxins induce vascular permeability, resulting in an inflammatory response (Rattmann et al 2008; Sade et al 2012) which is likely due to their ability to target mast cells, releasing histamine that can ultimately cause pain, edema, and erythema (Mulenga and Azad 2005; Sade et al 2012). Symptoms exhibited by TCTP toxins in noncnidarian lineages resemble that of thalassine, an uncharacterized component in sea anemone venom described early on in sea anemone venom research (Richet 1903a, 1903b, 1905).…”
Section: Discussionmentioning
confidence: 99%
“…A transcript resembling the TCTP was consistently expressed at high levels across all tissue types in our focal species (table 3) and also expressed at high levels previously in acrorhagi of A. elegantissima (see Macrander, Brugler, et al 2015). Venomous TCTP toxins induce vascular permeability, resulting in an inflammatory response (Rattmann et al 2008; Sade et al 2012) which is likely due to their ability to target mast cells, releasing histamine that can ultimately cause pain, edema, and erythema (Mulenga and Azad 2005; Sade et al 2012). Symptoms exhibited by TCTP toxins in noncnidarian lineages resemble that of thalassine, an uncharacterized component in sea anemone venom described early on in sea anemone venom research (Richet 1903a, 1903b, 1905).…”
Section: Discussionmentioning
confidence: 99%
“…the participation in the deadly cocktail of spider venoms. Two papers reported that translationally controlled tumour protein is a component of the venom from the brown spider Loxosceles intermedia (Gremski et al 2014;Sade et al 2012). Another one investigated the spit (used to 'glue' the prey to a solid surface) and the venom of the spider Scytodes thoracica using transcriptomic and proteomic analyses.…”
Section: Tctp In Arthropodsmentioning
confidence: 99%
“…Toxins including hyaluronidase, proteases, low molecular mass insecticidal peptides, Translationally Controlled Tumor Protein (TCTP) and phospholipases-D have been identified [1], [2], [13], [14], [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%